ANATOMY AS A FUNDAMENTAL SCIENCE IN MEDICINE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article provides an overview of anatomy as a fundamental branch of medical science. It discusses the main subfields of anatomy, including gross anatomy, microscopic anatomy, developmental anatomy, comparative anatomy, and clinical anatomy. The text emphasizes the importance of anatomical knowledge in medical education and clinical practice. Furthermore, it highlights how modern technology, such as MRI and 3D modeling, has enhanced the study of human anatomy. The article concludes by reinforcing the essential role of anatomy in understanding the structure and function of the human body.